SISTEM INFORMASI MANUFAKTUR DENGAN MATERIAL REQUIREMENT PLANNING DALAM KERANGKA KERJA SISTEM INFORMASI MANAJEMEN - Heri Kuswara (LPPM Universitas Bina Sarana Informatika, 2008)
A tights competition between companies nowadays is triggered by the speeding development of information technology. Each company must arm itself with the best information technology that can be integrated with its main infrastructures to handle all company’s business activities. Two information systems that can increase company’s performance is the Material Requirement Planning information system (MRP) and the Manufacturing Resource Planning (MRP II) is the best solution to any company in controlling its production components supply. Applying one or both of these information systems is proven significant to increase company’s competitive power.